Estimation of Fluoride Content of Drinking Water in Dharan - Koirala, Bandana; Niraula, Surya Raj; Ghimire, Anup (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Fluoride when present in drinking water at optimal level has been shown to promote oral health by preventing tooth decay. Dental caries represents a health problem that impacts on the medical, functional, nutritional and psychological status of patients in all the age groups. Fluoridation of public water supply is a safe, economical and effective measure to prevent dental caries. Objective: To estimate the level of fluoride present in drinking water supplies in all the wards of Dharan and to compare the fluoride concentration of its different water supply sources. Methods: One hundred water samples were collected from the various sources (ground water and surface water) and its different reservoirs along with random samples of 2-7 from all the wards of Dharan. The samples were then taken to the SEAM-N-MMA laboratory, Biratnagar to be tested for fluoride using the photometric method. Microsoft excel for data entry and SPSS 11.5 version for analysis were used. Significance of the variables was examined by Chi-square test. Results: The results of this study showed that in 96% of the samples taken, fluoride level was below the optimal. Only few samples met the lower range guideline value of Nepal (0.5 mg/l). Also, there was significant difference (p< 0.002) between the surface and consumer level fluoride. Conclusion: The fluoride content in drinking water supplies of Dharan was found to be below optimal level as per the national and WHO guideline values.